TEACHER'S NON-LANGUAGE COMMUNICATIVE COMPETENCE OF FOREIGN LANGUAGES IN THE CONTEXT OF THE EUROPEAN INTEGRATION PROCESS UKRAINE (Pedagogy of Higher and Secondary Education, 2008)
In the paper foreign language communicative competence of the teachers of foreign languages is discussed as a factor of success of Ukrainian integration into European educational sphere. The conditions of improvement of foreign language communicative competence developing process is presented in the system of in-service education.
Keywords: foreign language communicative competence; professional work of foreign language teacher; system of in-service education